2020
DOI: 10.17694/bajece.651286
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal and Aromatic Plants Identification Using Machine Learning Methods

Abstract: In this study, different machine learning (ML) methods were used to classify medicinal and aromatic plants (MAP) namely St. John's wort (Hypericum perforatum L.), Melissa (Melissa officinalis L.), Echinacea (Echinacea purpurea L.), Thyme (Thymus sp.) and Mint (Mentha angustifolia L.) based on leaf shape, gray and fractal features. Naive Bayes Classifier (NBC), Classification and Regression Tree (CART), K-Nearest Neighbor (KNN), and Probabilistic Neural Network (PNN) classification were used as methods. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Also, Sun et al (2017) used deep learning models to design plant classification in the natural habitats and they found that the achievement ratio of model was determined 91.78% (Sun et al, 2017). Similarly, Kayhan and Ergün (2020) classified the medicinal and aromatic plants by using several machine learning techniques and their results showed that plants were diagnosed in the correct classifications.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Sun et al (2017) used deep learning models to design plant classification in the natural habitats and they found that the achievement ratio of model was determined 91.78% (Sun et al, 2017). Similarly, Kayhan and Ergün (2020) classified the medicinal and aromatic plants by using several machine learning techniques and their results showed that plants were diagnosed in the correct classifications.…”
Section: Resultsmentioning
confidence: 99%
“…This database has also been classified with traditional methods (NBC, CART, KNN, and PNN methods), and it has been observed that a long processing time is required. 12 Despite this drawback, the CNN deep learning method provides high-accuracy test performances with three different training algorithms. In all three methods, none of these leaves is confused with the "2-thyme" leaf.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methods 12 Manual Manual Complex Proposed method Automatic Automatic Basic combines algorithms from a recurrent neural network and CNN and classifies the deep features extracted with the CNN model using classical classifiers. Our preliminary study 12 used NBC, CART, KNN, and PNN methods to classify the leaves from the database of medicinal and aromatic plants using their shape, and gray and fractal features. Liu et al 13 classified the Flavia leaf database, consisting of 32 species and 4800 leaves, with a 10-layer CNN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During calculation of the values of said concepts, the comparison of the estimated and available data is taken into account [33] Using the confusion matrix given in Figure 2, the accuracy values of the classification algorithms can be calculated. The precision statement is the ratio of the number of correct and positive estimated samples as class 1 to the number of estimated samples as class 1, as indicated in Equation ( 7) [34]. Sensitivity is defined as the ratio of the number of positive samples correctly classified in Equation ( 8) to the total number of positive samples.…”
Section: ) Data Mining Performance and Error Scales Analysismentioning
confidence: 99%